Development of an instructional video tutorial in teaching digital painting for fine arts students in St. Scholastica's College - Saldivar, Roland V. (Animo Repository, 2010)
The study focused on developing an instructional video tutorial in teaching digital painting for Fine Arts students in St. Scholasticas College. Using Hannafin and Pecks (1988) Instructional Design Model, the researcher followed three phases, namely, (1) Needs Assessment Phase, (2) Design Phase, and (3) Development and Implementation Phase. In each phase, evaluation and revisions were done. In the Needs Assessment Phase, the researcher studied students target competencies and topics to be covered based on the course syllabus. For the revision and evaluation, a survey was also conducted to 10 students who successfully completed the Digital Illustration course to determine the needed instructional material and teaching approach. The results suggested that the researcher focus on Digital Color Mixing and Blending with the aid of an instructional video tutorial. In the revision and evaluation under the Design Phase of the instructional video tutorial, the researcher conducted Task and Concept Analysis to determine the things that the student should learn to do. In the Development and Implementation Phase, the researcher organized the lesson flow, did the scriptwriting, storyboarding, and production of the video. Revision and evaluation was done based on the results of the survey conducted to 3 teacher-experts and 13 students. Except for some qualitative comments, the results of the survey showed that the respondents considered all the four domains (instructional, cosmetic, curriculum, and program adequacy) of the video tutorial as either adequate or highly adequate. The qualitative comments on the weaknesses (sound and music quality; use of captions and subtitles) of the first prototype were used as basis for revising the Final prototype. This final output was the revised prototype of the video tutorial that can run on different devices.